THE THEORY USING OF PIECEWISE-LINEAR UNIT TO FORMALIZE THE WORK OF REPAIR MODULES LINE OF REPAIR LINES WITH FLEXIBLE TRANSPORT SYSTEM - Myamlin, V. V. (Science and Transport Progress, 2008)
The method of formalization of the repair module work process of the car-repair flow line with flexible transport system is considered. As the mathematical scheme of process of the module functioning, the specific scheme of a piecewise-linear unit from the theory of units is offered. The given scheme can be put in a basis of development of imitating models for designing and research of the car-repair flow lines of new generation.